Adaptive Strategies: Algorithmic Analysis of Pre- and Post-Pandemic Manager-Frontline Employee Communication Model in Restaurants - Gutiérrez, María D. Lozano; Rojas López, Franco; Ochoa, Guadalupe Rovira (Ital Publication, 2024)
The aim of this study is to determine the impact of the COVID-19 pandemic on an independent restaurant chain in Puebla, Mexico, through longitudinal censuses with employees who had direct contact with diner guests (frontline employees) in 2019 and 2023. The survey data was analyzed through the algorithm Synthetic Minority Over-sampling Technique (SMOTE) to balance sample sizes and Information Gain to determine the dependence between the study variables. The results revealed the health crisis has led to changes in pivotal factors that drove better performance from frontline employees and managers in restaurants in Mexico. After the pandemic, frontline employees began to favor standard compliance due to the reinforcement of hygiene protocols. However, there are implications for the structure of teams and work styles on account of the decline in the number of frontline employees and the creation of multifunctional positions. Regarding the manager's factors, Linear Communication, which consists of providing clear and timely information, has become more relevant. While, there has been a decrease in Dynamic Communication oriented towards dialogue and Productive Communication focused on participation and the achievement of objectives. COVID-19 has accentuated the vulnerability of female frontline employees, who, since the pandemic, occupy multifunctional positions; the number of employees has decreased in greater proportion than the number of restaurants that have closed, impacting team dynamics; the most affected restaurants are located in automotive industrial parks, while restaurants in tourist or commercial areas have managed to maintain their workforce. The selected independent restaurant chain has focused on the functional aspects of the restaurant, as denoted by their current transactional leadership style and hierarchical organizational culture. However, there is an important theoretical implication related to the post-pandemic context, characterized by the presence of multifunctional roles and the pressure to meet customer service standards. Frontline employees have adopted individualistic behaviors, negatively impacting collaborative teamwork. These finding challenges existing literature that often emphasizes the positive aspects of employee empowerment and multifunctionality; it suggests that, under certain conditions, these factors may inadvertently hinder team cohesion and collaborative efforts. This study highlights the need to capitalize on Mexican restaurants by not only valuing the strategies from senior management but also by incorporating interpersonal perspectives from frontline employees to improve the organization in procedural and relational terms to adapt to future crises. Doi: 10.28991/ESJ-2024-08-05-021 Full Text: PDF